A Versatile System Simulation Environment for Millimeter-Wave Phased-Array FMCW-Radar Sensors for Automotive Applications - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference (APMC), 2011)
In this contribution a versatile system simulation environment for radar sensors being developed to operate in the automotive area is introduced. It combines a frontend simulation engine that is coupled in a co-simulation with a 3D ray-tracing tool to take the effects of the automotive radar channel into account, thus providing accurate and reliable results concerning the behavior of the implemented circuits in certain traffic situations. With respect to the latest developments in automotive radar, i.e. the transition from former comfort systems to current systems including an increased number of safety functions, the system simulation environment has been extended to support investigations on the phased-array radar principle. Applying this technique in the automotive area promises advantages in target detection in the vehicles vicinity by the means of increased hardware requirements, resulting in radar systems that are by far more difficult to design due to the number of side-effects that have to be additionally considered during the development process. To demonstrate the capability of this advanced simulation approach a typical traffic scenario is calculated showing not only the advantages of phased-array radar for the automotive field but also the performance of the simulation environment built up.
elib2cris::1512001600,dudek2011f